2009
DOI: 10.1128/aac.00909-08
|View full text |Cite
|
Sign up to set email alerts
|

Giardia , Entamoeba , and Trichomonas Enzymes Activate Metronidazole (Nitroreductases) and Inactivate Metronidazole (Nitroimidazole Reductases)

Abstract: Infections with Giardia lamblia, Entamoeba histolytica, and Trichomonas vaginalis, which cause diarrhea, dysentery, and vaginitis, respectively, are each treated with metronidazole. Here we show that Giardia, Entamoeba, and Trichomonas have oxygen-insensitive nitroreductase (ntr) genes which are homologous to those genes that have nonsense mutations in metronidazole-resistant Helicobacter pylori isolates. Entamoeba and Trichomonas also have nim genes which are homologous to those genes expressed in metronidazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 43 publications
4
81
0
1
Order By: Relevance
“…Although the precise mechanistic reasons for this counterintuitive observation remain to be determined, 5-NIs can be activated by different microbial pathways and probably target multiple microbial molecules (11,12,23) whose relative importance may depend on the compound and microbe. Because the specific target molecules of 5-NI drugs are not fully understood (23), a strategy focused on achieving effective whole-cell antimicrobial activity in the relevant systems may be the best choice for making rapid progress in developing improved antimicrobials in the clinically indispensable 5-NI class.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the precise mechanistic reasons for this counterintuitive observation remain to be determined, 5-NIs can be activated by different microbial pathways and probably target multiple microbial molecules (11,12,23) whose relative importance may depend on the compound and microbe. Because the specific target molecules of 5-NI drugs are not fully understood (23), a strategy focused on achieving effective whole-cell antimicrobial activity in the relevant systems may be the best choice for making rapid progress in developing improved antimicrobials in the clinically indispensable 5-NI class.…”
Section: Discussionmentioning
confidence: 99%
“…Mz resistance is functionally heterogeneous, with several causative mechanisms for each of the target microbes and between different microbes (7,24). For example, resistance in Giardia involves down-regulation of nitro drug-activating systems, including different reductases and redox proteins and metabolites (11,25), whereas Trichomonas also produces resistance proteins that directly detoxify nitro drugs (12) and Bacteroides has transporters that can remove nitro drugs from the cell (26). Despite this mechanistic diversity, for each of the resistant microbes, we were able to identify nitro compounds that could combat resistance, and some compounds were broadly effective against different resistant microbes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nitroreductase enzyme assay was carried out according to the method described by Pal et al (2009). The reaction mixture comprised of Tris-acetate (100 mM Tris-HCl, 50 mM acetate buffer, pH 7.0), 30 µM metronidazole as a substrate, half MIC of different drugs as inhibitors, 0.3 mM NADPH or NADH and enzyme in a 1 mL reaction volume.…”
Section: Nitroreductase Enzyme Assaymentioning
confidence: 99%
“…On the other hand, trichomoniasis, a sexually transmitted disease associated with vaginitis, cervicitis, urethritis, prostatitis, epididymitis, cervical cancer, and infertility, accounts for 180 million infections acquired annually worldwide (Ali and Nosaki, 2007;Nanda et al, 2006). E. histolytica, T. vaginalis, and G. lamblia infections are mainly treated with imidazole type drugs, but it has been reported that these three protist pathogens have developed drug resistance (Upcroft and Upcroft, 2001;Pal et al, 2009). This has produced an urgent need for more efficient and safer antiprotozoal agents.…”
Section: Introductionmentioning
confidence: 99%